Stress and resilience: associations of stress biomarkers with different conceptualizations of resilience - Ringgold, Veronika; Rohleder, Nicolas (Current Opinion in Behavioral Sciences, 2025)
We provide readers with an overview of the literature on stress and resilience and their relationship to biomarkers of stress systems. We emphasize the need for precise definitions and operationalizations and the importance of considering the complexity of the stress and resilience constructs. Research on stress and resilience in conjunction with stress biomarkers is scarce, and longitudinal designs are lacking. However, some associations of stress biomarkers with resilience were found. These point toward a protective effect of resilience against the biological stress consequences. In this context, a clearer picture emerges for inflammation compared to cortisol. Finally, we point toward the need of longitudinal research, making use of sophisticated statistics and integration of individual perceptions into research designs. Future research is needed to map the complexity of stress and resilience, individually and in conjunction.
CRIS-Team Scopus Importer:2025-02-17